Water Saving In Industry - Elza Tursunova (Global Scientific Publishing, 2024)
The process of increasing shortage of fresh water resources is happening everywhere, affecting all types of needs of society and nature. One of the important aspects of water conservation and ways to reduce the volume of fresh water consumption in an enterprise and the amount of wastewater discharged in industry is the method of reuse or recycling of wastewater, which consists in returning purified wastewater to the technological process and cooling system in industrial refrigeration units . The article discusses aspects of improving the water supply of industrial enterprises that are relevant for industrial complexes of Uzbekistan by introducing methods for reusing industrial wastewater
Keywords: water issues; industrial wastewater; production